Strength and status of dental specialty societies in Nepal - Koirala, PK; Pradhan, S; Shrestha, R; Bhochhibhoya, A; Thapa, A; Karn, G; Sigdel, B (Journal of Nepalese Prosthodontic Society, 2021)
Introduction: It’s been over a decade since different dental speciality societies have been established in Nepal. These specialities have generated important human resource, which have contributed to uplift dental care syatem in Nepal. The study was designed with the objective of assessing strength and status of dental specialities in Nepal. Materials and Methods: The cross-sectional observational study was conducted from October 2020 to December 2020. Nepal Medical Council (NMC) websites, dental specialities websites as well as personal communication with responsible persons of the dental societies were assessed to collect data. Demographic and professional details, specialist number, age, gender, work place, place of graduation and graduation year were entered into Microsoft Excel Sheet. Data was analyzed based upon frequency distribution and percentage. Result: According to NMC record, total number of dental specialists in dentistry is 616, till December 2020. Out of them, 451 specialists were registered with the dental societies, who were included in this study. There were 6 speciality dental societies in Nepal and most of the societies were a decade old and had more than 50 members. Orthodontics association was the oldest with 164 members. The highest number of specialists were in the age group 30-40 year in all the dental specialties and they were mostly working in Kathmandu valley. Conclusion: Different dental speciality societies have been growing throughout the country which have produced qualified manpower for providing specialized dental services. These societies are contributing towards achieving goals of better oral health care delivery in the nation.